The effect of the preoperational psychoeducation program for Taiwanese breast cancer patients: A three-month follow-up study - Jui-Ko Hung; Wen-Hung Kuo; Chang-Chang Tseng; Yih-Ru Cheng; Chih-Hsun Wu (Elsevier, 2022)
Objective: Studies suggest that psychosocial interventions might be more effective during highly stressful periods, such as before surgery. This study aimed to explore the effectiveness of the Preoperational Health Psychology Education program among Taiwanese breast cancer patients. Methods: A total of 137 adult women (1) diagnosed with breast cancer; and (2) admitted to the ward for surgery were recruited to join the program one day before surgery. Emotional distress, worries, and cancer self-efficacy were evaluated at admission, post-program, and 3-month post-surgery. Patients were grouped into high/low distress groups, and mixed-design ANOVA was used to examine the program's effectiveness. Results: The results showed significant interactions of Group × Time in emotional distress (F = 16.15, p = .000) and worry (F = 5.81, p = .005), but not in self-efficacy (F = 2.97, p = .068). The post-hoc tests revealed significant decreases in emotional distress and worry in the high distress group. Conclusion: The program was found helpful in reducing emotional distress and worries. The effect lasting for three-month for those with higher preoperational emotional distresses. Innovation: This psycho-education program with a relatively rare one-session design, targeted at a less-studied pre-surgery period, is helpful to a less-studied population, Asian cancer patients.